Exploring EFL Students in Peer-Assisted Practice Using Online Dictionary : A Case Study in Speaking Classroom - Lestari, Yulia; Pujiawati, Nia; Puspitaloka, Nina (IKIP Siliwangi, 2025)
This qualitative research explores peer-assisted learning strategies in vocational school settings, focusing on students' challenges and perceptions in practicing English pronunciation. The study addresses the need for effective speaking skills among vocational students, considering linguistic differences and the influence of mother tongue. Through a case study approach involving multimedia majors, data was collected via classroom observations and structured interviews, analyzed thematically to reveal insights into students' use of online dictionaries and their perceptions of peer assistance. To examine the impact of peer-assisted strategies on English pronunciation skills and collaborative learning perceptions among vocational students. Utilizing qualitative case study design with multimedia students, data collected through observations and interviews highlighted reliance on online dictionaries and varied peer capabilities. Students actively use online dictionaries to enhance pronunciation and collaborative learning. Challenges include peer capabilities and individual learning preferences affecting strategy effectiveness. Peer-assisted strategies, coupled with technology, significantly improve vocational students' English pronunciation. Effective integration requires tailored support and flexible methodologies. Educators should enhance peer-support skills, design collaborative activities, and leverage technology for optimal language learning outcomes.